Reproductive outcomes after TCRS in patients with incomplete and complete uterine septum: a retrospective cohort study - Yang, Jian; Li, Cong-Qing; Xia, Jing-Xian; Zhu, Wen-Jing; Wang, Jing; He, Wei; Wang, Qing-Yuan; Wang, Wen-Yan (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to evaluate the effects of transcervical resection of the septum (TCRS) on reproductive outcomes in women of reproductive age with two types of uterine septa.MethodsIn this retrospective cohort study, we evaluated the reproductive outcomes after TCRS in 87 women with an incomplete uterine septum and 35 women with a complete uterine septum. The study was conducted from January 2010 to December 2020 at the Second Affiliated Hospital of Anhui Medical University in China.ResultsIn Group A (incomplete uterine septum), TCRS markedly decreased the rates of spontaneous abortion and embryonic arrest (p < 0.001) while significantly enhancing the likelihood of term delivery (p < 0.001). Similarly, Group B (complete uterine septum) observed a substantial increase in pregnancy rates (from 43.5 to 82.6%), a significant decrease in spontaneous abortions (p < 0.05), and an improvement in term delivery rates (p < 0.001) post-surgery. The dimension of the septum in cases of Group A did not affect the outcome of adverse reproductive events. However, cesarean section rates were significantly higher in Group B than in Group A (76.5% vs. 47.7%). The optimal time to achieve pregnancy was within the first year for Group A and the 12th month for Group B after TCRS.ConclusionIn patients undergoing TCRS, a notable decrease in spontaneous abortion rates was observed, alongside an increase in pregnancy and full-term birth rates. However, there was a concomitant rise in cesarean section rates. Furthermore, our findings indicate that patients with an incomplete uterine septum are more likely to conceive earlier than those with a complete uterine septum following surgery, thereby optimizing the timing for pregnancy.